2017
DOI: 10.3390/ijms18081708
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection of Mosquitoes with Chikungunya and Dengue Viruses Reveals Modulation of the Replication of Both Viruses in Midguts and Salivary Glands of Aedes aegypti Mosquitoes

Abstract: Arthropod-borne virus (arbovirus) infections cause several emerging and resurgent infectious diseases in humans and animals. Chikungunya-affected areas often overlap with dengue-endemic areas. Concurrent dengue virus (DENV) and chikungunya virus (CHIKV) infections have been detected in travelers returning from regions of endemicity. CHIKV and DENV co-infected Aedes albopictus have also been collected in the vicinity of co-infected human cases, emphasizing the need to study co-infections in mosquitoes. We thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 35 publications
3
60
0
Order By: Relevance
“…This is because mosquitoes can feed multiple times on more than one human host and require multiple bites per each gonotrophic cycle (Harrington et al, 2014). Concomitant infections were reported in studies by Göertz et al (2017), Rückert et al (2017), Le Coupanec et al (2017) and Vazeille et al (2010). However, their reports are conflicting on the aspect of vector competence.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is because mosquitoes can feed multiple times on more than one human host and require multiple bites per each gonotrophic cycle (Harrington et al, 2014). Concomitant infections were reported in studies by Göertz et al (2017), Rückert et al (2017), Le Coupanec et al (2017) and Vazeille et al (2010). However, their reports are conflicting on the aspect of vector competence.…”
Section: Discussionmentioning
confidence: 82%
“…Aegypti mosquitoes could be infected with and transmit all combinations of these viruses simultaneously. In a study by Le Coupanec et al (2017), it was demonstrated that mixed infection of Chikungunya and Dengue viruses facilitated viral replication in Aedes aegypti thus increasing in their numbers before exit. It is worth noting that arboviruses can share a geographical area or overlap.…”
Section: Resurgence or Emergence Of Epidemic Arboviral Diseasesmentioning
confidence: 99%
“…Moreover, the effect of coinfections on mosquito physiology has been addressed just recently [2, 98, 99]. Thus, so far we only have a partial view on the processes involved in vector susceptibly and transmission for arboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…During the extrinsic incubation period (EIP), a virus that enters the mosquito midgut and is able to pass into the hemolymph may infect fat body cells, trachea, hemocytes, ovaries, nerve tissue, and reach salivary glands [2, 18, 32, 33]. For an arbovirus to be transmitted to a new vertebrate host in a subsequent blood meal, it must first be secreted with the saliva by the acinar (epithelial) cells to the luminal side of the salivary glands.…”
Section: Infection Of a Aegypti Mosquitoesmentioning
confidence: 99%
See 1 more Smart Citation